2019
DOI: 10.3174/ajnr.a6061
|View full text |Cite
|
Sign up to set email alerts
|

The Occipital Emissary Vein: A Possible Marker for Pseudotumor Cerebri

Abstract: BACKGROUND AND PURPOSE: Transverse sinus stenosis can lead to pseudotumor cerebri syndrome by elevating the cerebral venous pressure. The occipital emissary vein is an inconstant emissary vein that connects the torcular herophili with the suboccipital veins of the external vertebral plexus. This retrospective study compares the prevalence and size of the occipital emissary vein in patients with pseudotumor cerebri syndrome with those in healthy control subjects to determine whether the occipital emissary vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…From anatomical point of view, if we refer to the proposed classification system (Figure 3d), an OEV should rarely found having a short course andmaking a direct anastomosis through a complete OEF, which connects a dural sinus with an extracranial vein. In the imaging studies, however, even a longer intraosseous anastomosis is called as OEV, [15] although it should be In (a) the diploic vein is drained to both dural sinus and occipital vein; in our series corresponding IOF+EOF were found in 13.3% of the skulls. In (b) the occipital diploic vein drains only to the occipital vein through EOF (8%).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…From anatomical point of view, if we refer to the proposed classification system (Figure 3d), an OEV should rarely found having a short course andmaking a direct anastomosis through a complete OEF, which connects a dural sinus with an extracranial vein. In the imaging studies, however, even a longer intraosseous anastomosis is called as OEV, [15] although it should be In (a) the diploic vein is drained to both dural sinus and occipital vein; in our series corresponding IOF+EOF were found in 13.3% of the skulls. In (b) the occipital diploic vein drains only to the occipital vein through EOF (8%).…”
Section: Resultsmentioning
confidence: 62%
“…In a MRI study on axial images, Cakmak et al [14] reported the OEV in 28% of the cases examined. In another imaging study on subtracted CT venography and contrast enhanced MRI, Hedjoudje et al [15] examined the OEV and reported its presence in 65.2% of the patients with increased pressure in the transverse sinus system versus 31.5% of the patients without pressure signs. Interestingly, however, the whole study is based on an identifiable occipital anastomosing vein connecting the confluence of sinuses or distal part of the superior sagittal sinus with the occipital vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between IIH and venous pressure is further supported by the findings of Hedjoudje et al, who observed an occipital emissary vein in 30 of 46 (65%) patients with IIH versus only 29 of 92 (32%) of healthy controls and found it to be larger on average in patients versus controls. 19 Furthermore, the mean emissary vein diameter was reduced following stenting in 17 patients. These findings suggest that this vein, which connects the torcula with the suboccipital veins, can dilate to serve as a collateral pathway in patients with IIH who have TS stenosis, and that its enlargement may serve as yet another radiological marker of the disease.…”
Section: The Role Of Collateral Cortical Veins In the Pathophysiologymentioning
confidence: 96%
“…Arteriovenous shunting can produce a similar effect. Emissary veins can also function as collaterals and dilate in individuals with craniosynostosis, particularly when associated with jugular foramen stenosis or atresia, and in cases of pseudotumor cerebri . Occasional anatomic variants, such as diminutive bilateral jugular veins, may cause emissary veins to dilate as they function as collateral venous drainage…”
Section: Dural Venous Sinus Variations and Related Pathologymentioning
confidence: 99%